PENGENDALIAN DAN PENGELOLAAN TERHADAP AKTIVA TETAP - Hastuti, Rini Tri; M Bintang Prajogi; Yordan P (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The purpose of this activity is to link the community service activities with the Road Map in the Research RIP and Camel PKM [1]. Providing literacy on how to manage assets in a business/entrepreneurship venture. This asset management can be applied in the asset rental business. [2]. This material was provided after conducting a survey which found that many of the students' family backgrounds had asset rental businesses. The problem that we found at partner, especially among students majoring in Social Sciences class 12, was that they only received accounting material up to trading company accounting. Therefore, we want to provide a solution by providing a choice of several additional materials. And it was agreed that the fixed asset accounting material was chosen for the following reasons: First, the fixed assets material was not yet included in the accounting subject matter. Second, in several interviews conducted, information was obtained that the student's family background had a business in vehicle rental services and housing (boarding/renting). So it is hoped that this training can provide additional knowledge and knowledge on how to manage fixed assets (assets) efficiently and effectively. The specific aims and targets to be achieved from this training are so that students of partner can understand how to record and report fixed asset accounting in the company's financial reports. For this reason, we, lecturers from the Faculty of Economics, will provide training which is planned to be divided into three stages, namely: planning stage, implementation stage, and review stage. At the planning stage, we came to partner to conduct a preliminary survey by interviewing teachers and the school principal. From this survey, we found training topics that suited partner needs and we prepared a proposal to LPPM. Next, at the implementation stage, we carry out training by preparing training materials in the form of modules which will be distributed during face-to-face training. The training lasted for one day. Finally, at the review stage, we will give quizzes and distribute questionnaires to students to determine their level of understanding of this topic. The output targets to be achieved for this training activity are: Obligatory output in the form of publication in the Serina journal and additional output in the form of HKI.